The Weekend Effect in Septic Shock Patients Using the Nationwide Emergency Department Sample Database. Issue 6 (December 2021) - Bou Chebl, Ralphe; Kattouf, Nadim; Assaf, Mohamad; Abou Dagher, Gilbert; Kassir, Alaa; Mahmassani, Dina; Bachir, Rana; El Sayed, Mazen
ABSTRACT: Background: The weekend effect is the increased mortality in hospitalized patients admitted on the weekend. The aim of this study was to examine the effect of weekend admissions on septic shock patients. Methods: This is a retrospective observational study of the 2014 Nationwide Emergency Department Sample Database. Septic shock patients were included in this study using ICD-9-CM codes. Descriptive analysis was done, in addition to bivariate analysis to compare variables based on admission day. Multivariate analysis was conducted to examine the association between admission day and mortality in septic shock patients after adjusting for potential confounding factors. Results: A total of 364, 604 septic shock patients were included in this study. The average age was 67.19 years, and 51.1% were males. 73.0% of patients presented on weekdays. 32.3% of septic shock patients died during their hospital stay. After adjusting for confounders, there was no significant difference in the emergency department or in-hospital mortality of septic shock patients admitted on the weekend compared with those admitted during weekdays, (OR = 1.00 [95% CI: 0.97–1.03], P value = 0.985). Conclusion: There was no statistically significant difference in overall mortality between septic shock patients admitted on the weekend or weekday. Our results are contradictory to previous studies showing an increased mortality with the weekend effect. The previous observations that have been made may not stand up with current treatment protocols.